2007
DOI: 10.1248/cpb.55.1006
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Doxorubicin with Oleate Ions: Fluorescence Spectroscopy and Liquid-Liquid Extraction Study

Abstract: Doxorubicin (DOX) is an antineoplastic agent of the anthracycline family used as a first-line treatment in numerous neoplastic diseases, particularly in breast cancer.1) The progression of tumor cell resistance, in particular multidrug resistance (MDR), is one of the main factors which limit its employment.2) MDR is generally associated with a decreased intracellular accumulation of drug related to a membrane glycoprotein, the P-gp that contributes to a rapid expelling of the drug from the cell.3) An interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…These results were similar to values obtained in previous studies using other magnetic carriers, such as chitosan-coated magnetite nanoparticles (18 wt.%) [17] and magnetic polymersomes (12 wt.%) [67]. In aqueous solution, DOX molecules adopt different conformations depending on the solution pH ( Figure S3, supporting information) [68]. At pH 6, it is expected that drug loading is promoted by electrostatic interactions between the primary amine groups of DOX and the sulfonate groups of the carrageenan.…”
Section: Doxorubicin Loadingsupporting
confidence: 90%
“…These results were similar to values obtained in previous studies using other magnetic carriers, such as chitosan-coated magnetite nanoparticles (18 wt.%) [17] and magnetic polymersomes (12 wt.%) [67]. In aqueous solution, DOX molecules adopt different conformations depending on the solution pH ( Figure S3, supporting information) [68]. At pH 6, it is expected that drug loading is promoted by electrostatic interactions between the primary amine groups of DOX and the sulfonate groups of the carrageenan.…”
Section: Doxorubicin Loadingsupporting
confidence: 90%
“…This result strongly suggested that positively charged drug molecules are bound to negatively charged CA-MNP through electrostatic interactions. The impressive affinity of doxorubicin for negatively charged molecules such as oleate ions and phospholipids has been the subject of numerous earlier investigations [37][38][39][40]. The interaction of DOX molecules with CA-MNP was also evident from the predominant quenching of DOX fluorescence in presence of CA-MNP (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…2,[40][41][42][43] We have performed zeta-potential and fluorescence spectroscopic studies to explore the binding of DOX with PPNM. DOX a cationic drug used in chemotherapy is chosen as a model drug to estimate the drug loading and release behavior of PPNM.…”
Section: Characterizationsmentioning
confidence: 99%